Lifelong Learning and Sexual Health Literacy in Nursing Students: Cross-Sectional Study - Nihal Aloğlu; Ayla Güllü (Sakarya Üniversitesi Holistik Sağlık Dergisi)
Objective: Lifelong learning and sexual health literacy are two separate concepts that are important in improving health today. The aim of this study is to determine the relationship between sexual health literacy and lifelong learning in nursing students.Methods: 269 individuals were involved in this cross-sectional investigation. An online poll was used to gather data between August 10 and September 10, 2023. The "Life-long Learning Scale" and the "Sexual Health Literacy Scale" were employed in the research. The data analysis techniques included post-hoc testing, ANOVA, T-tests, and basic linear regression studies.Results: The mean age of the participants was 21.62±2.41. Of the students, 77.3% were female, 97.8% were single, and 36.1% were in third grade. A moderate, positive, and substantial connection was found between the variables based on a simple linear regression analysis conducted between the scales (R=0.470, R2=0.221, F=75.776, p=0.000). Life-long learning tendency explained 22% of sexual health literacy.Conclusions: Lifelong learning has a significant impact on sexual health literacy. It is recommended that the necessary programs be prepared, implemented and closely monitored to increase the tendency for lifelong learning in educational institutions.